2017
DOI: 10.1002/prp2.324
|View full text |Cite
|
Sign up to set email alerts
|

Noncompetitive inhibition of human CYP2C9 in vitro by a commercial Rhodiola rosea product

Abstract: A commercial Rhodiola rosea (R. rosea) product has previously demonstrated CYP2C9 inhibition in humans. The purpose of this study was to provide in vitro inhibitory data for this particular interaction and to classify the mechanism of the interaction. Another aim was to examine the in vitro influence of ethanol on the CYP2C9 activity. Human CYP2C9 (wild type) isolated from a baculovirus‐infected cell system was incubated with 0.8 μmol/L losartan for 20 min. Sulfaphenazole was used as a positive control. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The positive control reversible inhibitors all reduced their respective P450 enzyme activity ( Fig. 3; Table 8) in a manner consistent with the literature (Ring et al, 1996;Suzuki et al, 2002;Emoto et al, 2003;Walsky et al, 2006;VandenBrink et al, 2011;Zhao et al, 2012;Thu et al, 2017). CAW-R61J was found to be a relatively weak reversible inhibitor for most of the P450s tested.…”
Section: Resultssupporting
confidence: 84%
“…The positive control reversible inhibitors all reduced their respective P450 enzyme activity ( Fig. 3; Table 8) in a manner consistent with the literature (Ring et al, 1996;Suzuki et al, 2002;Emoto et al, 2003;Walsky et al, 2006;VandenBrink et al, 2011;Zhao et al, 2012;Thu et al, 2017). CAW-R61J was found to be a relatively weak reversible inhibitor for most of the P450s tested.…”
Section: Resultssupporting
confidence: 84%
“…The results of herb–drug interaction studies of various adaptogens are contradictory 1–4,598,626–628 . Interactions with some CYP isoenzymes have been observed in vitro studies only in high concentrations of herbal extracts that are far beyond their blood levels when taken in the standard therapeutic doses and not associated with active markers 1,598,626–628 .…”
Section: Challenges and Regulatory Issuesmentioning
confidence: 99%
“…It was suggested that these phenolic compounds (rosavin, rosarin, rosin, salidroside/rhodioloside, and tyrosol) have no impact on activity of CYP450 enzymes and do not inhibit CYP3A4, CYP2D6, or CYP1A2 ( Hellum et al, 2010 ; Xu et al, 2013 ; Thu et al, 2016a ). The presence of minor amounts of herbacetin rhamnosides (rhodiosin and rhodionin) may presumably induce inhibition of CYP2D6 ( Xu et al, 2013 ) in some commercial preparations of Rhodiola ( Thu et al, 2016b , 2017 ).…”
Section: Introductionmentioning
confidence: 99%